Research on the Coupling Relationship between Professional Clusters and Industrial Clusters in the Pearl River Delta Region of China - Li Li; Yuzhou Hu; Sisi Zheng; Yimian Lin (Discrete Dynamics in Nature and Society)
The development of education should serve the needs of economic and social development by providing high-quality and appropriate professionals for economic development. Recently, the implementation of Double High Plan has provided many opportunities for the cultivation of high-level professional groups. In the process of professional group construction, the extent of coupling between the level of professional group construction and the level of regional economic clusters is an important evaluation. This work is based on the list of proposed projects for the construction of high-level professional clusters in Guangdong Province between 2019 and 2021. This list is issued by the department of education of Guangdong Province. The quantitative indicators and coupling models are established to estimate the degree of coupling between the construction of professional clusters in 9 prefecture-level cities located in the Pearl River Delta region and the level of regional industrial clusters. The results presented in this work show that the professional cluster construction and industrial construction level of four prefecture-level cities, including Guangzhou, Shenzhen, Foshan, and Dongguan, achieve coordinated development, while the remaining areas are mostly in transformation and integration stages. This is because the development level of industrial clusters has surpassed the construction of professional clusters in universities, resulting in a mismatch between talent cultivation and the requirements of economic development. This mismatch is manifested in three aspects. First, the supply and demand do not align in terms of the scale of professional groups and industrial clusters. Second, insufficient integration of professional clusters and industrial clusters. Finally, this mismatch is evident in imbalanced resource allocation. The fit between the setting of professional clusters and the structure of industrial clusters is not high. Based on the aforementioned analysis, this work presents suggestions for promoting the integration of industry and education and school-enterprise cooperation among universities in the Pearl River Delta region. This will eventually enhance the construction of high-level professional groups in the Pearl River Delta region and result in coordinated economic and social development.